2009
DOI: 10.1111/j.1749-6632.2009.04153.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Air Pollution on Ecosystems and Biological Diversity in the Eastern United States

Abstract: Conservation organizations have most often focused on land-use change, climate change, and invasive species as prime threats to biodiversity conservation. Although air pollution is an acknowledged widespread problem, it is rarely considered in conservation planning or management. In this synthesis, the state of scientific knowledge on the effects of air pollution on plants and animals in the Northeastern and Mid-Atlantic regions of the United States is summarized. Four air pollutants (sulfur, nitrogen, ozone, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
95
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 184 publications
(110 citation statements)
references
References 179 publications
3
95
0
6
Order By: Relevance
“…Lovett et al (2009) clearly showed that all ecosystems types are affected by the air pollution; it affects both the aquatic and terrestrial habitats, which are expected to be of benefits to man. Biodiversity in Lagos is mostly affected by the insensitive landuse changes due to the increase in population.…”
Section: Loss Of Biodiversitymentioning
confidence: 99%
“…Lovett et al (2009) clearly showed that all ecosystems types are affected by the air pollution; it affects both the aquatic and terrestrial habitats, which are expected to be of benefits to man. Biodiversity in Lagos is mostly affected by the insensitive landuse changes due to the increase in population.…”
Section: Loss Of Biodiversitymentioning
confidence: 99%
“…Most developing nations have been influenced by atmospheric pollution, in terms of human health (Anderson et al, 2012), climate change (Kan et al, 2012) and loss of biodiversity (Lovett et al, 2009). With urban transport development, traffic-derived pollutants become an increasing problem (Walsh and Shah, 1997;Ning and Sioutas, 2010;Cao et al, 2015) and have been linked to respiratory and cardiovascular disease, birth and developmental defects, cancer (Hei, 2010) and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding these impacts is crucial because they can result in altered species abundance, plant community composition (Payne et al 2013) and reduced biodiversity (Stevens et al 2004). Ombrotrophic (rain fed) bogs are nutrient poor and obtain their entire N budget from deposition, making them particularly sensitive to N deposition (Bobbink et al 1998;Lovett et al 2009). Carnivorous plants are typical of ombrotrophic bogs (Givnish et al 1984) which makes them sensitive to changes in nutrient availability, for example through the effects of increased atmospheric N deposition .…”
Section: Introductionmentioning
confidence: 99%